2018
DOI: 10.1021/acsomega.8b02087
|View full text |Cite
|
Sign up to set email alerts
|

Computational Assessment of Chemical Saturation of Analogue Series under Varying Conditions

Abstract: Assessing the degree to which analogue series are chemically saturated is of major relevance in compound optimization. Decisions to continue or discontinue series are typically made on the basis of subjective judgment. Currently, only very few methods are available to aid in decision making. We further investigate and extend a computational concept to quantitatively assess the progression and chemical saturation of a series. To these ends, existing analogues and virtual candidates are compared in chemical spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…As designed, these scores are robust and practically insensitive to the number of VAs that are used, provided VAs outnumber EAs by at least two to three times [ 2 4 ]. Furthermore, the choice of chemical reference spaces for compound distance calculations is variable and can be modified according to the characteristic features and requirements of specific optimization efforts.…”
Section: Methodology: From Como To Deepcomomentioning
confidence: 99%
See 1 more Smart Citation
“…As designed, these scores are robust and practically insensitive to the number of VAs that are used, provided VAs outnumber EAs by at least two to three times [ 2 4 ]. Furthermore, the choice of chemical reference spaces for compound distance calculations is variable and can be modified according to the characteristic features and requirements of specific optimization efforts.…”
Section: Methodology: From Como To Deepcomomentioning
confidence: 99%
“…This is the scientific context in which the Compound Optimization MOnitor (COMO) methodology evolved. One of the roots of COMO was the development of a scoring scheme to evaluate chemical saturation of compound series on the basis of biological screening data [ 1 , 2 ]. Modifying and extending this scoring scheme and combining it with the assessment of SAR progression then gave rise to the introduction of the COMO approach [ 3 5 ], which was originally designed as a diagnostic.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical space analysis of individual analog series has been carried out to measure progression in lead optimization and saturation of analog series (Kunimoto et al, 2018; Vogt et al, 2018; Yonchev et al, 2018). Nevertheless, the fact that assumption (iii) makes analog series inconsistent in as much as the scaffold definition is dependent on the dataset used (Bajorath, 2018) is a limitation for the exploration of chemical space of multiple analog series at once.…”
Section: Methodsmentioning
confidence: 99%
“…In light of this situation, the method development efforts discussed herein chart new territory. [6][7][8][9][10] They ultimately led to the compound optimization monitor (COMO) approach [9,10] that integrates chemical saturation and SAR diagnostics with the prediction of candidate compounds. The following discussion of the theory and scoring schemes is primarily tailored towards a computational audience.…”
mentioning
confidence: 99%
“…A systematic investigation of analysis and scoring parameters revealed that saturation scores were essentially stable for feature spaces of different composition and VA populations covering a wide range. [7] Chemical saturation scoring was further refined and combined with another numerical scoring scheme accounting for SAR progression. [8] The basic principles underlying chemical saturation scoring discussed above were further extended as follows.…”
mentioning
confidence: 99%